Qualitative Research in the EFL Setting: Portraying Students' Problems and Actions - Fatimah, Asri Siti; Saputra, Yuyus; Khairunnisa, Syifa (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
This study examines the problems encountered by EFL students in composing qualitative research proposals and explores the tactics employed to address these problems. The study included three individuals who were enrolled as students in the English Education Department and had experienced delays in submitting their qualitative research proposals. The data were obtained via semi-structured interviews, wherein the researcher utilized mobile phones to record the participants' responses. The research employed a descriptive case study methodology and applied thematic analysis for data analysis. The findings of this study revealed a number of challenges encountered by students. These challenges encompassed deficiencies in various writing components, such as content-related problems, syntactic issues, vocabulary limitations, and challenges in sourcing references. Additionally, students faced internal obstacles, specifically a lack of motivation stemming from laziness. Lastly, technical difficulties were encountered when undertaking qualitative research proposals. In order to address these challenges, several potential solutions have been identified. One such solution involves fostering a supportive environment among peers, wherein they provide encouragement and assistance in the process of writing proposals. Additionally, it has been suggested that students may benefit from engaging in activities that restore their motivation and enthusiasm for research, such as watching educational content on platforms like YouTube. Lastly, self-evaluation has been proposed as a means of assessing their progress and identifying areas for improvement.Keywords: Qualitative Research, EFL, Challenges and Solutions